Maternal mortality risk indicators: Case-control study at a referral hospital in Guinea. (August 2020) - Diallo, Abdourahamane; Michalek, Irmina Maria; Bah, Ibrahima Koussy; Diallo, Ibrahima Amadou; Sy, Telly; Roth-Kleiner, Matthias; Desseauve, David
Highlights: We described exposures linked with a higher risk of intra-/postpartum maternal death in Guinea. The risk was mainly associated with transfer from another hospital and misoprostol-induced labor. Other risk indicators included, non-use of partogram, duration of labor ≥24 h, and history of C35 section. Abstract: Objective: This study aimed to describe intrapartum and postpartum exposures possibly associated with the risk of in-hospital maternal mortality in Guinea. Study Design: Data were collected in the Western Sub-Saharan Africa setting at the university hospital in Conakry, Guinea, during 2016−2017. Case-control study design was applied. The cases comprised all intrapartum and postpartum maternal deaths recorded during the study period. The controls were selected by random sampling from patients discharged alive following hospitalization due to vaginal delivery or cesarean section. Maternal mortality ratio (MMR) was defined as a quotient of the number of maternal deaths per 100, 000 live births. Multivariable logistic regression was applied to generate odds ratios (OR) and 95 % confidence intervals (95 %CI). Results: A total of 10, 208 live births and 144 maternal deaths were recorded. The MMR was at 1411 per 100, 000 live births. The main causes of maternal death included postpartum hemorrhage (56 %), retroplacental hematoma (10 %), and eclampsia (9%). The ORs of maternal death were significantly elevated in case of transfer from another hospital (OR 24.60, 95 %CI 11.32–53.46), misoprostol-induced labor (OR 4.26, 95 %CI 2.51–7.91), non-use of partogram (OR 3.70, 95 %CI 1.31–5.20), duration of labor ≥24 h (OR 2.87, 95 %CI 1.35–5.29), and positive history of cesarean section (OR 2.54, 95 %CI 1.12–6.19). Conclusion: To stop preventable maternal mortality in Sub-Saharan Africa, continued efforts are needed to provide perinatal monitoring, to reorganize the obstetric reference system, and to decrease the number of avoidable cesarean sections. Furthermore, the internal supervision of misoprostol doses used for labor induction should be a priority.